Drug information handbook : with international trade names index - American Pharmacists Association; Lexi-Comp, Inc ([Hudson, Ohio] : Lexi-Comp, 2016)
The Drug Information Handbook with International Trade Names index, 25th Edition, contains most of the industry-Ieading pharmacology content from the Lexicomp Drug Information Handbook, plus Canadian and multinational drug monographs for use worldwide.
Includes index
Keywords: Drugs -- Handbooks, manuals, etc; Clinical pharmacology -- Handbooks, manuals, etc